Aspectos do ensino de Matemática nos Ginásios Vocacionais paulistas: integração de disciplinas e Matemática Moderna Teaching and learning Math in the Vocational Gymnasiums: some remarks on curricular integration and New Math Movement - Nakamura, Maria Eliza Furquim Pereira; Garnica, Antônio Vicente Marafioti (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2018)
O artigo trata do ensino de Matemática nos Ginásios Vocacionais, instituições paulistas de ensino secundário criadas em 1961 e extintas pelo Regime Militar em 1968. Alguns aspectos gerais, relativos à proposta pedagógica dessas escolas, são apresentados de modo a sustentar a discussão mais especifica sobre os dois temas centrais neste artigo: o modo como a Matemática operava num contexto em que a integração de disciplinas era um principio fundamental; e a influência da Matemática Moderna nessa instituição. The so called Ginásios Vocacionais (Vocational Gymnasiums) were an institution created in São Paulo State (Brazil) in 1962 and extinguished by the Brazilian Dictatorial Government in 1968. The main intention of this paper is to discuss some features of the teaching and learning of Mathematics in such schools. Some data on the general educational context are presented in order to support the discussion about the two central issues of this article: the role of Mathematics in a curricular framework in which integration among disciplines was one of the main principles; and the influence of New Math in these Gymnasiums. This paper is based in a research developed using Oral History as its main methodological guide.